Kryzys prawa karnego? Strategia polityczno-kryminalna współczesnych Włoch: [Crisis of criminal law? Political and criminal strategy in present day Italy] (Studia Prawnicze / The Legal Studies, 1984)
The author discusses political and criminal strategy of Italy during the last 15 yeas. He considers it in the context of basic problems of modern criminal policy, thus the considerations are of a more universal character. He emphasizes in particular the breakdown of liberalistic resocializing trends of special prevention of the 60s and convertion to retributive positions of general prevention. While analyzing such features of Italian criminal policy as legislative dynamics, differentiation, depenalization and decriminalization, the tuthor comes to the conclusion that they are by no means manifestation of a crisis of criminal law or its inconsistency, but, on the contrary, manifestation of its consistency and its adjustment to new economic, social and political conditions. Thus, the structures of power effectively counteract the pressure of social forces demanding the revision of the structure of powers by means of new legal instruments adequate to the new situation. The aim of depenalization and decriminalization was not to lessen State control over the citizen, but, on the contrary, to make it more strict by using new effective measures in new social conditions.